Autologous Blood Versus Suture Conjunctival Limbal Graft as Pterygium Surgery Treatment - Putu Budhiastra (Majalah Oftalmologi Indonesia, 2018)
Introduction and Objective: A Pterygium is an elevated, superficial, external ocular mass that usually forms over the perilimbal conjungtiva and extends onto the corneal surface. A Pterygium can cause a significant alteration in visual function in advanced cases. It become inflamed, resulting in redness and ocular irritation. Pterygium excision surgery has been using many methods. There are three choices of method to attach the graft: by suturing, fibrin glue or autologous blood. The purpose of this study is to learn about the efficacy of autologous blood versus suturing conjungtival limbal graft (CLG) on pterygium excision surgery Methods: Retrospective study of 18 patients underwent Pterygium excision surgery with autologous blood gluing compared to suturing the graft. Six patients underwent CLG surgery with suturing and 12 patients were treated with autologous blood gluing. Suturing process was done with nylon 10-0 and the suture was released 7 days after surgery, whereas the graft on the patient with autologous blood CLG was placed and left there for about 10 minutes. Both groups were evaluated after day 1, 1st week, 2nd week and 1st month. Any report of irritating sensation, graft loss, and healing process were recorded thoroughly. Result: Patients with sutured CLG were complaining of uncomfortable sensation on their cornea until one week before suture was released, all grafts were attached until a month. Out of 12 patients with autologous blood CLG method, there were no complain of irritability on cornea until a week, 4 patients lost the graft on the first day, two patients grew granuloma on the second week, 10 patients start healing on the second week. Conclusion: There are still limitations to pterygium excision with autologous blood CLG compared to pterygium excision with CLG suture technique.